Analysis of the Lexical Composition of the Russian Language: the Problem of Storing Words and Extracting Words from Communication in the Modern Environment (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Based on an extensive corpus of texts, our article analyzes the lexical composition of the modern Russian language in the context of globalization and the dominance of English. We identify semantic evolutions and reductions in the use of words; conduct a comparative analysis with historical data, emphasizing the dynamics of changes. Our research highlights the importance of preserving the lexical richness and unique cultural nuances of the Russian language. We focus on the role of the native language in the formation of cultural values and propose measures to preserve it in the modern world in order to preserve the linguistic heritage for future generations and enrich the diversity of cultural expressions.